Адаптивний метод і алгоритм пошуку центрів кластерів за допомогою нейронної мережі - Стех, Ю.В.; Файсал М.Е. Сардіх; Лобур, М.В.; Домброва, М.С.; Арцибасов, В.Є. (Моделювання та інформаційні технології, 2010)
Developed an adaptive method and algorithm for finding the cluster centers by using neural network. The developed method requires a set threshold. Proposed heuristic computational formula for determining the optimal value of threshold. An experimental study of the algorithm is given. Developed an algorithm for modifying the value of a threshold, which allows you to determine the best centers of the clusters.